Interferons in the treatment of myeloproliferative neoplasms - Pankit Vachhani; John Mascarenhas; Prithviraj Bose; Gabriela Hobbs; Abdulraheem Yacoub; Jeanne M. Palmer; Aaron T. Gerds; Lucia Masarova; Andrew T. Kuykendall; Raajit K. Rampal; Ruben Mesa; Srdan Verstovsek (Therapeutic Advances in Hematology, 2024)
Interferons are cytokines with immunomodulatory properties and disease-modifying effects that have been used to treat myeloproliferative neoplasms (MPNs) for more than 35 years. The initial use of interferons was limited due to difficulties with administration and a significant toxicity profile. Many of these shortcomings were addressed by covalently binding polyethylene glycol to the interferon structure, which increases the stability, prolongs activity, and reduces immunogenicity of the molecule. In the current therapeutic landscape, pegylated interferons are recommended for use in the treatment of polycythemia vera, essential thrombocythemia, and primary myelofibrosis. We review recent efficacy, molecular response, and safety data for the two available pegylated interferons, peginterferon alfa-2a (Pegasys) and ropeginterferon alfa-2b-njft (BESREMi). The practical management of interferon-based therapies is discussed, along with our opinions on whether to and how to switch from hydroxyurea to one of these therapies. Key topics and questions related to use of interferons, such as their safety and tolerability, the significance of variant allele frequency, advantages of early treatment, and what the future of interferon therapy may look like, will be examined. Pegylated interferons represent an important therapeutic option for patients with MPNs; however, more research is still required to further refine interferon therapy.